The T‐type calcium channel blocker Z944 reduces conditioned fear in Genetic Absence Epilepsy Rats from Strasbourg and the non‐epileptic control strain. (8th April 2019) - Marks, Wendie N.; Zabder, Nadine K.; Greba, Quentin; Cain, Stuart M.; Snutch, Terrance P.; Howland, John G.
Abstract: Genetic Absence Epilepsy Rats from Strasbourg (GAERS) are a rodent model of childhood absence epilepsy (CAE) that display a gain‐of‐function mutation in the gene encoding the Cav3.2 T‐type calcium channel. GAERS demonstrate heightened learning and delayed extinction of fear conditioning. Our objective in the present study was to examine the effects of the pan‐T‐type calcium channel blocker Z944 on the acquisition, consolidation and extinction of conditioned fear in GAERS and the non‐epileptic control (NEC) strain. Z944 (10 mg/kg; ip) was administered 15 min prior to either acquisition, extinction day 1 (24 hr later), acquisition and extinction day 1, or during the consolidation (post‐acquisition) of tone‐cued fear conditioning. Extinction was examined 24 and 48 hr after conditioning. In drug naïve GAERS, increased freezing during the acquisition and extinction phases of fear conditioning was found. Short‐term effects of Z944 on performance were observed as Z944 increased freezing during testing on the day it was administered. Z944 administered prior to the acquisition phase had a long‐term effect on extinction. Specifically, both GAERS and NECs showed a decrease in freezing during extinction relative to drug naïve GAERS and NEC rats respectively. Regardless of strain or treatment, female rats showed reduced extinction of fear relative to male rats. These results demonstrate that T‐type calcium channels contribute to the neural systems that mediate the learning and memory of conditioned fear. Overall, these findings suggest that T‐type calcium channel blockers show promise in the treatment of learning impairments observed in disorders such as CAE. Abstract : Treatment with the T‐type calcium channel blocker Z944 prior to the acquisition of fear conditioning decreased freezing in Genetic Absence Epilepsy Rats from Strasbourg during the extinction phases to levels comparable to non‐epileptic controls (NECs). NECs treated with Z944 also showed reduced freezing during extinction; however, the results suggest that NECs have impaired recall of conditioned fear as little freezing behaviour was observed during extinction trials.